Volcanic structures investigation through SAR and seismic interferometric methods: The 2011–2013 Campi Flegrei unrest episode - Pepe, S.; De Siena, L.; Barone, A.; Castaldo, R.; D'Auria, L.; Manzo, M.; Casu, F.; Fedi, M.; Lanari, R.; Bianco, F.; Tizzani, P. (Remote sensing of environment, 2019)
Observations from satellites provide high-resolution images of ground deformation allowing to infer deformation sources by developing advanced modeling of magma ascent and intrusion processes. Nevertheless, such models can be strongly biased without a precise model of the internal structure of the volcano. In this study, we jointly exploited two interferometric techniques to interpret the 2011–2013 unrest at Campi Flegrei caldera (CFc). The first is the Interferometric Synthetic Aperture Radar (InSAR) technique, which provides highly-resolved spatial and temporal images of ground deformation. The second is the Ambient Noise Tomography (ANT), which images subsurface structures, providing the constraints necessary to infer the depth of the shallow source at CFc (between 0.8 and 1.2 km). We applied for the first time a tool to delineate the deformation source boundaries from the observed deformation maps: the Total Horizontal Derivative (THD) technique. The THD processes the vertical component of the ground deformation field detected through InSAR applied to COSMO-SkyMed data. The patterns retrieved by applying the THD technique show consistent spatial correlations with (1) the seismic group-velocity maps achieved through the ANT and (2) the distribution of the earthquakes nucleated during the unrest at ~1 km. High-velocity anomalies, the retrieved geometrical features of the deformation field, and the spatial distribution of seismicity coincide with extinct volcanic vents in the eastern part of the caldera (Solfatara/Pisciarelli and Astroni). Such a coincidence hints at a significant role of the extinct plumbing system in either constraining or channeling the eastward propagation of magmatic fluids. Here, we demonstrated that a joint analysis of the InSAR patterns, seismic structures, and seismicity allows us to model in space and time the characteristics and nature of the shallow deformation source at CFc. Using published literature, we show that the effects of structural heterogeneities at shallow depths may have a more significant early-stage impact on the evolution of the surface displacement signals than deeper magmatic sources: these secondary structural effects may produce local amplification in the deformation records which can be mistakenly interpreted as early signals of impending eruptions. The achieved results are particularly relevant for the understanding of the origin of deformation signal at volcanoes where magma propagation within sills is expected, as at CFc. •The joint exploitation of InSAR and ANT allow to detect the source features.•Interferometric technique is Synthetic Aperture Radar to the surface analysis.•The Ambient Noise Tomography to analyze the internal structures.•We analyze di Campi Flegrei caldera during the 2011–2013 unrest episode.